Ideality of beauty (Materiali di Estetica. Terza serie, 2017)
The cornerstones of the Western notion of beauty, from ancient philosophy to the aesthetics of the last three decades, seem to say that it has quite a stable core. The article argues that this core consists in the most surprising power which beauty appears to have: the power of fulfilling even our imagination, that is, the power of making us undergo the aesthetic experience of a satisfactory relationship between the reality we observe and the ideality we imagine, and, through its example, the power of making us work on the development of our reality. If this is true, then the reason why beauty has been, is, and will possibly be exceedingly important is that, by making us undergo the aesthetic experience of recognizing something ideal into something real, it can be the clearest symbol of our possibility, and even hope, of working on an ideal human measure of both our identity and our relationship with nature and the realm of artifacts.